SARS-CoV-2: Cytokine storm relationship in the development of endothelial lesions in severe cases of COVID-19 (Research, Society and Development, 2023)
In March 2020, was declared by OMS the COVID-19 pandemic. Having SARS-CoV-2 as the etiological agent, the virus has in its protein envelope spicular glycoproteins capable of binding to ACE2 protein receptors present mainly in lung cells, endothelial cells of the cardiovascular system, in addition to mediating cell entry fusion. By making this connection with the ACE-2 receptor, the viral envelope fuses with the cell membrane and then viral replication begins, inciting a hyperinflammatory state, generating the “cytokine storm”. In patients with endothelial disorders, there may be an increase in thrombin, coagulation and exacerbation of inflammation, leading to a greater consumption of endogenous anticoagulants and decreasing their production through HF1-alpha blockade. This condition leads the patient to a pro-thrombotic state, triggering poor prognosis and pulmonary thromboembolism, for example. This bibliographic review aims to analyze how endothelial lesions can contribute to severe cases of COVID-19, aiming at compiling clinical information and its close relationship with the cytokine storm. Severe cases of COVID-19 are associated with endothelial dysfunction, inflammation and cytokine production and release, promoting increased leukocyte adherence, activation of the procoagulant and anti-fibrinolytic state, which can lead to multiple organ failure and further facilitate clotting. disseminated intravascular hyperinflation associated with coagulopathy and thrombocytopenia. A quick and correct diagnosis is necessary for the use of therapeutic strategies that favor the reestablishment of the hemodynamic balance and clinical improvement of the patient in serious condition.